Characteristics of respiratory outbreaks in care homes during four influenza seasons, 2011–2015. Issue 2 (June 2018) - Gallagher, N.; Johnston, J.; Crookshanks, H.; Nugent, C.; Irvine, N.
Summary: Background: Influenza and other respiratory infections can spread rapidly and cause severe morbidity and mortality in care home settings. Aim: This study describes the characteristics of respiratory outbreaks in care homes in Northern Ireland during a four-year period, and aims to identify factors that predict which respiratory outbreaks are more likely to be positively identified as influenza. Methods: Epidemiological, virological, and clinical characteristics of outbreaks during the study period were described. Variables collected at notification were compared to identify predictors for an outbreak testing positive for influenza. t -Tests and χ 2 -tests were used to compare means and proportions respectively; significance level was set at 95%. Findings: During the four seasons, 95 respiratory outbreaks were reported in care homes, 70 of which were confirmed as influenza. More than 1000 cases were reported, with 135 associated hospitalizations and 22 deaths. Vaccination uptake in residents was consistently high (mean: 86%); however, in staff it was poorly reported, and, when reported, consistently low (mean: 14%). Time to notification and number of cases at notification were both higher than expected according to national recommendations for reporting outbreaks. No clinically significant predictors of a positive influenza outbreak were identified. Conclusion: Respiratory outbreaks in care homes were associated with significant morbidity and mortality, despite high vaccination uptake. The absence of indicators at notification of an outbreak to accurately predict influenza infection highlights the need for prompt reporting and laboratory testing. Raising staff awareness, training in the management of respiratory outbreaks in accordance with national guidance, and improvement of staff vaccination uptake are recommended.